Formation, structure and properties of biocompatible TiZrHfNbTa high-entropy alloys. Issue 6 (3rd June 2019) - Yuan, Yuan; Wu, Yuan; Yang, Zhi; Liang, Xue; Lei, Zhifeng; Huang, Hailong; Wang, Hui; Liu, Xiongjun; An, Ke; Wu, Wei; Lu, Zhaoping
ABSTRACT: Biocompatibility of HEAs in the TiZrHfNbTa system in which all the constituents are non-toxic and allergy-free was scrutinized systematically, and novel biomechanical materials with a unique combination of low modulus (57 GPa, almost half that of conventional biomedical titanium alloys), good mechanical biocompatibility and low magnetic susceptibility (1.71 × 10 −6 cm 3 g −1, similar to that of pure Zr) were successfully developed. Moreover, the underlying mechanisms responsible for phase formation and promising properties were explored. This work not only offers a series of novel bio-metallic materials with prominent properties for practical applications, but also shed light on understanding of phase formation and strengthening of HEAs in general. GRAPHICAL ABSTRACT: IMPACT STATEMENT: Several biocompatible TiZrHfNbTa HEAs with prominent properties for practical applications were developed and the relevant alloy design principles were revealed.